(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
Freedom is our own right. The individual struggle for freedom has been going on for ages. When India was under British rule, the individual struggle turned into a mass struggle. August 15, 1947, our country India got freedom under British rule. in exchange for the blood, struggle and sacrifice of many patriots. India was under British rule for almost two hundred years, after the 76 years of independence, that history stirs our minds. However, this swaraj- gain did not happen in a day, many freedom fighters became fighters and revolutionaries in the freedom movement without caring about their lives. Also the people of the country have joined the freedom movement in various ways. Society has seen freedom Swaraj in different perspectives. As we know, extremist (Dadabhai Naoraji, Gopalkrishna Gokhale, and Surendranath Bandyopadhyay etc.) and moderate (Bal Gangadhar Tilak, Lala Lajpat Roy, Bipinchandra Pal etc.) two groups were formed. That is there was a point- of- view difference. In the literary world, there are many writings on the topic of freedom. Many writers and Rabindranath Tagore writings have emerged. We all know that Rabindranath was an eyewitness. This nationalism influenced the novel ’Gora’. He has participated in everything from holding meetings in the Swadeshi Movement in Kolkata to taking to the streets to encourage people to wear Swadeshi clothing. But Rabindranath broke and reconnected his ideas almost all the time, which was influenced by the novel ’Gora’. it is clear evidence of what was Rabindranath’s spirit about the Swadeshi movement. He doesn’t believe Indians all rules and regulations should be accepted immediately. Just as the good of one’s country should be immediately accepted, the bad should also be discarded. His national identity is universal. How and through which direction this national entity became universal is the subject of this essay.